Evaluation of Anti-inflammatory, Anti-pyretic, Analgesic, and Hepatoprotective Properties of Terminalia macroptera - Haïdara, Mahamane; Dénou, Adama; Haddad, Mohamed; Camara, Aïssata; Traoré, Korotoumou; Aubouy, Agnès; Bourdy, Geneviève; Sanogo, Rokia (Planta Medica International Open, 2020)
In Mali, improved traditional medicines [“Médicaments Traditionnels Améliorés”] are prepared from traditionally used medicinal plants. Recently, the Department of Traditional Medicine has identified Terminalia macroptera Guill. & Perr. (Combretaceae) as a potential candidate for an improved traditional medicine. T. macroptera is a West African medicinal plant used in Mali against various health disorders, with more than 30 different indications mentioned by traditional healers, including hepatitis, gonorrhea, fever, pain relief, and various infectious diseases (Helicobacter pylori-associated diseases). To date, validation of most of the biological activities of has been mainly carried out in vitro, except for antimalarial activities. In this study, the potential anti-inflammatory, antipyretic, analgesic, and hepatoprotective properties of T. macroptera were investigated in different murine models. Administration of T. macroptera ethanolic root and leaf extracts in rats significantly reduced pyrexia, pain, inflammation, and hepatic marker enzymes such as alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase in the different murine models used (p<0.05). A phytochemical screening of T. macroptera revealed the presence of tannins, flavonoids, saponins, anthracene derivatives, sterols, triterpenes, and sugars in both leaf and root extracts as the main phytochemical compounds. This was confirmed by qualitative analysis, liquid chromatography coupled with high-resolution mass spectrometry. T. macroptera extracts demonstrated interesting in vivo antipyretic, analgesic, anti-inflammatory, and hepatoprotective activities. Therefore, T. macroptera should be proposed and further evaluated as a potential improved traditional medicine for the treatment of liver-related disorders and for the relief of pain and fever.
Keywords: Terminalia macroptera; Combretaceae; Médicaments Traditionnels Améliorés/improved traditional medicines; medicinal plant antipyretic; anti-inflammatory; hepatoprotective